A Comparative Study of Child Custody Under Islamic and Nigerian Laws - Uthman Abdulhameed; Daud Olalekan Abdulsalam; Abolore Muhammad-Awwal Ishaq; Saheed Adewale Badmus (Al-Mahkamah: Islamic Law Journal, 2025)
Child custody cases have been attended to differently in term of jurisdiction within the frame of Islamic and Nigeria laws. Although like Sharīᶜah, Nigeria laws also emphasize the importance of the interest of the child, despite this, there are numerous dissimilarities that lie between the Islamic and Nigeria laws on the issue of child custody. Therefore, this paper aimed at analyzing the differences that are inherent in the two laws with a view to showcasing the similarities and dissimilarities. It also aimed to assess the Islamic principles governing child custody, including the factors considered in determining the most suitable guardian, the rights and responsibilities of the custodian, and the legal procedures involved. The paper adopted descriptive and analytical methods of research in carrying out the study. The descriptive method was used in explaining how child custody is being maintained under Islamic and Nigerian laws while analytical method was used to discuss the similarities and dissimilarities between the two laws. The paper revealed that the common similarity between them on child custody is in the area of interests of the child in choosing his custodian. It also found that Nigeria law always gives priority to father in most cases in Nigerian customary law except where the child has not reached the age of puberty. The paper concluded that the parents are custodians of their children and are responsible for them before Allah. Therefore, the paper recommended that couples should find possible means of avoiding separation and when it becomes necessary the interest of the children should be given priority.